Comparative analysis of nursing and midwifery regulatory and professional bodies' scope of practice and associated decision‐making frameworks: a discussion paper. (13th April 2015) - Kennedy, Catriona; O'Reilly, Pauline; Fealy, Gerard; Casey, Mary; Brady, Anne‐Marie; McNamara, Martin; Prizeman, Geraldine; Rohde, Daniela; Hegarty, Josephine
Abstract Aims To review, discuss and compare nursing and midwifery regulatory and professional bodies' scope of practice and associated decision‐making frameworks. Background Scope of practice in professional nursing and midwifery is an evolving process which needs to be responsive to clinical, service, societal, demographic and fiscal changes. Codes and frameworks offer a system of rules and principles by which the nursing and midwifery professions are expected to regulate members and demonstrate responsibility to society. Design Discussion paper. Data sources Twelve scope of practice and associated decision‐making frameworks (January 2000–March 2014). Implications for nursing Two main approaches to the regulation of the scope of practice and associated decision‐making frameworks exist internationally. The first approach is policy and regulation driven and behaviour oriented. The second approach is based on notions of autonomous decision‐making, professionalism and accountability. The two approaches are not mutually exclusive, but have similar elements with a different emphasis. Both approaches lack explicit recognition of the aesthetic aspects of care and patient choice, which is a fundamental principle of evidence‐based practice. Conclusion Nursing organizations, regulatory authorities and nurses should recognize that scope of practice and the associated responsibility for decision‐making provides a very public statement about the status of nursing in a given jurisdiction.